Acute Toxicity and Behavioral Alterations as Biomarkers of Triclosan Exposure in Blue Tilapia Oreochromis aureus (Steindachner, 1864) - Hameed, Iman; Al-Faiz, Nawras; Al-yassein, Rajaa (Iraqi Journal of Aquaculture, 2026)
Several behavioral changes were observed in blue tilapia upon exposure to triclosan (0.15, 0.5, 1, 1.5, 2, 2.5, and 3 mg/L) for 96 hours. The severity of these behavioral changes increased with concentration. Fish exhibited rapid swimming, rapid fin movements, abnormal operculum movements, attempts to ascend, and vertical jumps towards the water surface. They also showed loss of balance, respiratory distress, and capsizing. Over 96 hours of exposure, triclosan exhibited concentration-dependent toxicity, resulting in a progressive, proportional increase in fish mortality. Neither the control treatment nor the 0.15 mg/L treatment showed any mortality. However, at higher concentrations, 20% of fish in the 0.5 mg/L treatment, 40% in the 1 mg/L treatment, and 65% in the 1.5 mg/L treatment died. Increasing the triclosan concentration to 2 mg/L resulted in 85% mortality. The highest mortality rate (100%) was recorded in the 3 mg/L treatment.